Osmanlı ve erken Cumhuriyet kadın dergileri (1., 2. ve 3. c. İstanbul 4. c. İstanbul 5. c. İstanbul 6. c. İstanbul)
6 cilt (1. c. 575 sayfa ; 2. c. 260 sayfa ; 3. c. 404 sayfa ; 4. c. 667 sayfa ; 5. c. 699 sayfa ; 6. c. 624 sayfa)